Social norms and elections: How elected rules can make behavior (in)appropriate - Arno Apffelstaedt; Jana Freundt; Christoph Oslislo (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
Can elections change people's ideas about what is ethically right and what is wrong? A number of recent observations suggest that social norms can change rapidly as a result of election outcomes. We explore this conjecture using a controlled online experiment. In our experiment, participants rate the social appropriateness of sharing income with poorer individuals. We compare situations in which a rule has been elected that asks people to share or not to share, respectively, with situations in which no rule has been elected. In the absence of an election, sharing is widely considered socially appropriate, while not sharing is considered socially inappropriate. We show that elections can change this social norm: They shift the modal appropriateness perception of actions and, depending on the elected rule, increase their dispersion, i.e. erode previously existing consensus. As a result, actions previously judged socially inappropriate (not sharing) can become socially appropriate. This power prevails, albeit in weaker form, even if the election is subject to controversial practices such as vote buying or voter disenfranchisement. Drawing on behavioral data from another experiment, we demonstrate that election-induced norm shifts predict behavior change.
Keywords: D02; D91; C91; 330; social norms; elections; prosocial behavior; rule compliance